2012
DOI: 10.1590/s1679-62252012005000003
|View full text |Cite
|
Sign up to set email alerts
|

Study of sodium arsenite induced biochemical changes on certain biomolecules of the freshwater catfish Clarias batrachus

Abstract: Toxic impact of sublethal concentration (1 mg/L; 5% of 96h LC 50 value) of sodium arsenite (NaAsO 2 ) on certain biomolecules (proteins, nucleic acids, lipids, and glycogen) of five tissue components (muscles, liver, brain, skin, and gills) of the freshwater catfish Clarias batrachus was analysed. The important toxic manifestations include marked decrease in the concentration of proteins (21.72-45.42% in muscles; 3.42-53.94% in liver; 15.39-45.42% in brain; 15.40-4.00% in skin and 11.35-64.13% in gills), .01% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…Although much evidence were not observed in presence of Na2HAsO4 on the enhancement of triglyceride, the previous study reveals that arsenic, a potent toxic and heavy element causes the similar effects regarding the synthesis of lipids in liver of fresh water fish (Kumar and Banerjee, 2012). The lipid accumulation, as indicated by the increased number and size of red-stained lipid droplets, was detected in the liver of arsenic-treated fish (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although much evidence were not observed in presence of Na2HAsO4 on the enhancement of triglyceride, the previous study reveals that arsenic, a potent toxic and heavy element causes the similar effects regarding the synthesis of lipids in liver of fresh water fish (Kumar and Banerjee, 2012). The lipid accumulation, as indicated by the increased number and size of red-stained lipid droplets, was detected in the liver of arsenic-treated fish (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 79%
“…The increased synthesis of cholesterol also may induce higher liver weight and fatty liver and cause lipogenesis as demonstrated by Kumar and Banerjee (2012). In separate experiments, groups of fish were exposed to Na2HAsO4 for 1 h and cholesterol contents in liver were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…The total protein content in the hepatopancreas, muscle and gill were found to decline in the sub-lethal concentration of potassium permanganate. Kumar et al (2012) reported that sodium arsenide decreased in the concentration of protein in catfish Clarius batractus. Mahajan and Zambare, (2001) reported decrease in protein contents in the fresh water bivalve Corbicula striatella after heavy metal stress most of the time.…”
Section: Discussionmentioning
confidence: 99%
“…Puffer fish used in our experiments were 6-montholds, 15 ± 2 cm in length, 120 ± 10 g in weight, and all from the same batch. A fluoride ion concentration of 35 mg/L was selected for this proteomics experiment because this is the concentration known to induce fluorosis and also sublethal to the 16-cm catfish previously reported by Kumar et al [16]. Sixteen puffer fish were randomly divided into two groups, with eight fish in each group.…”
Section: Preparation Of Puffer Fishmentioning
confidence: 99%
“…Fluoride can also induce endoplasmic reticulum (ER) stress and inhibit protein synthesis and secretion [14,15]. Recently, significant depletion of total protein and lipids has been observed in the liver of catfish after exposure to excessive fluoride [16]. Apoptosis and destruction of the normal cell cycle by fluoride have also been reported during organ culture of mouse fetal long bones [17].…”
Section: Introductionmentioning
confidence: 99%